Isoalantolactone Induces Cell Cycle Arrest, Apoptosis and Autophagy in Colorectal Cancer Cells - Li, Junkui; Zhu, Peili; Chen, Yifei; Zhang, Shiqing; Zhang, Zhu; Zhang, Zhang; Wang, Ying; Jiang, Xiaoli; Lin, Kaili; Wu, Wei; Mo, Zhixian; Sze, Stephen Cho Wing; et al. (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is an aggressive cancer. Isoalantolactone (IATL) has been reported to exert cytotoxicity against various cancer cells, but not CRC. In this study, we explored the anti-CRC effects and mechanism of action of IATL in vitro and in vivo. Our results demonstrated that IATL inhibited proliferation by inducing G0/G1 phase cell cycle arrest, apoptosis and autophagy in CRC cells. Repression of autophagy with autophagy inhibitors chloroquine (CQ) and Bafilomycin A1 (Baf-A1) enhanced the anti-CRC effects of IATL, suggesting that IATL induces cytoprotective autophagy in CRC cells. Mechanistic studies revealed that IATL lowered protein levels of phospho-AKT (Ser473), phospho-mTOR (Ser2448), phospho-70S6K (Thr421/Ser424) in CRC cells. Inhibition of AKT and mTOR activities using LY294002 and rapamycin, respectively, potentiated the inductive effects of IATL on autophagy and cell death. In vivo studies showed that IATL suppressed HCT116 tumor growth without affecting the body weight of mice. In consistent with the in vitro results, IATL lowered protein levels of Bcl-2, Bcl-XL, phospho-AKT (Ser473), phospho-mTOR (Ser2448), and phsopho-70S6K (Thr421/Ser424), whereas upregulated protein levels of cleaved-PARP and LC3B-II in HCT116 tumors. Collectively, our results demonstrated that in addition to inhibiting proliferation, inducing G0/G1-phase cell cycle arrest and apoptosis, IATL initiates cytoprotective autophagy in CRC cells by inhibiting the AKT/mTOR signaling pathway. These findings provide an experimental basis for the evaluation of IATL as a novel medication for CRC treatment.